Identification of Human Memory‐Like NK Cells. Issue 1 (5th January 2017) - Kovalenko, Elena I.; Streltsova, Maria A.; Kanevskiy, Leonid M.; Erokhina, Sophia A.; Telford, William G.
Abstract: Our understanding of NK biology is increased dramatically, a product of improved flow‐cytometric techniques for analyzing these cells. NK cells undergo significant changes in repertoire during differentiation. A repeating stimulus, such as a cytomegalovirus infection, may result in accumulation of certain types of highly differentiated NK cells designated as memory‐like, or adaptive NK cells. Adaptive NK cells are capable of rapid expansion and effective response to the recall stimulus. These cells differ significantly from conventional NK cells both functionally and phenotypically. Here we describe an approach for identification and analysis of adaptive NK cells in human peripheral blood. CD57‐positive cells with high expression of activating‐receptor NKG2C, increased expression of KIR receptors, lack of co‐expression with inhibitory receptor NKG2A, and decreased expression of activating receptor NCR3 (NKp30) all characterize this cell type. The flow‐cytometric method described below can identify this NK cell subset on a relatively simple flow cytometer. © 2017 by John Wiley & Sons, Inc.